(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
Glutathione S-transferases (GSTs) regard mainly multifunctional proteins included into various intracellular events like stress metabolism, both primary metabolism and secondary metabolism, herbicide detoxification process in addition to plant defense oppose heavy metals, ozone destroy and xenobiotic. They consider mainly cytoplasmic enzymes which can be dissolved. Up to now, the crystal structures of More than two hundred of soluble GSTs, that are found into the bacteria, animals in addition to plants are determined. The function of them is affected by crystal structure of GSTs. Both glutathione-s transferases and plant glutathione transferases, actually are consist of many kinds. The types of glutathione transferases (GSTs) and Plant glutathione transferases possess several using by both divergent and convergent paths, phylogenetic studies indicates that every soluble GSTs originated essentially from the old progenitor gene.